Бременские музыканты: [сказки : для детей дошкольного возраста] (Серия "3 любимых сказки", 2017)
Экземпляры: ф.10 (20191213) / Инвентарный номер: 44302 / Цена: / Сис.шифр: Д / Авт.знак: Б 87 / ГРНТИ: 17.82.93 / ББК: Д